2015
DOI: 10.1136/gutjnl-2015-309889
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for bile acid diarrhoea in functional bowel disorder with diarrhoea: a systematic review and meta-analysis

Abstract: Overall, the test with the highest diagnostic yield conducted in the largest number of studies was SeHCAT retention, which is not widely available in many countries outside Europe and Canada. Using different diagnostic tests, 25% (average) of patients with lower FBD with diarrhoea has evidence of idiopathic BAD. These tests serve to identify idiopathic BAD among patients with FBD with diarrhoea. Further studies are required to appraise the performance characteristics of tests for idiopathic BAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 54 publications
2
102
0
12
Order By: Relevance
“…3 There is an expectation that physicians should try to reduce these costs by making a positive diagnosis of IBS, using symptom-based diagnostic criteria, whilst simultaneously minimizing invasive investigations. 4,5 Physicians may be reluctant to adopt this approach in clinical practice, as GI diseases manifest as a limited repertoire of symptoms, and those of IBS can mimic organic diseases such as inflammatory bowel disease, 6 microscopic colitis, 7 bile acid diarrhea, 8,9 or celiac disease. 10 The current "gold standard" for symptom-based diagnosis of IBS are the Rome III criteria, 1 but these have only been validated in one large study from Canada, 11 and performed modestly in distinguishing IBS from organic GI disease.…”
Section: Irritable Bowel Syndrome (Ibs) Is a Chronic Functional Gastrmentioning
confidence: 99%
“…3 There is an expectation that physicians should try to reduce these costs by making a positive diagnosis of IBS, using symptom-based diagnostic criteria, whilst simultaneously minimizing invasive investigations. 4,5 Physicians may be reluctant to adopt this approach in clinical practice, as GI diseases manifest as a limited repertoire of symptoms, and those of IBS can mimic organic diseases such as inflammatory bowel disease, 6 microscopic colitis, 7 bile acid diarrhea, 8,9 or celiac disease. 10 The current "gold standard" for symptom-based diagnosis of IBS are the Rome III criteria, 1 but these have only been validated in one large study from Canada, 11 and performed modestly in distinguishing IBS from organic GI disease.…”
Section: Irritable Bowel Syndrome (Ibs) Is a Chronic Functional Gastrmentioning
confidence: 99%
“…Other recent studies provide evidence on both the reliability of tauroselcholic ( 75 selenium) acid as a diagnostic tool and the increasing use of the test in clinical practice 6 9 19. Valentin et al reported results from a large systematic review and meta-analysis carried out to identify a biomarker for idiopathic BAD in patients with functional bowel disorder with diarrhoea 19. They identified 36 studies that enrolled >5000 patients and analysed data for four different BAD tests.…”
Section: Introductionmentioning
confidence: 99%
“…Of these four tests, the authors concluded that tauroselcholic ( 75 selenium) acid had the highest diagnostic yield (table 1). 19 …”
Section: Introductionmentioning
confidence: 99%
“…Defective BA uptake into ileal mucosal biopsies has been excluded as a cause of BA diarrhea ( 3 ). Th e literature shows that 25-40% of patients with functional diarrhea or diarrhea-predominant irritable bowel syndrome (IBS-diarrhea) have evidence of excessive hepatic BA synthesis or markers of excess BA excretion ( 4 ).…”
mentioning
confidence: 99%